THE IMPACT OF BIG DATA ON FINANCIAL REPORTING - Agustinus Winoto; Meiryani Meiryani; Reyhan Reyhan (Bina Nusantara University, 2023)
Big data analytics can influence financial accounting by collecting, recording, and managing data and preparing financial reports. Big data provides convenience and speed of access to transaction data streams. By using big data, accountants in an organization can access transaction information more quickly and can work on large-scale transactions. This study aims to examine the influence of big data on financial reporting with Quantitative Evidence from Indonesia. This research uses quantitative methods. The data used in this study are primary data obtained from the study subject in the form of a questionnaire. The data obtained is processed using SPSS 25. The results of the hypothesis test stated that the analysis of big data has an effect on the quality of the report. This means big data technology as a resource internally owned company can improve the company's financial performance.